Stabilizing fine-grained soil by electrically injecting Ca2+, CO32-, and HPO42- ions - Rustamaji, R M; Priadi, Eka (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
This paper presents a new technique that can electrically inject stabilizing ions, which can be used to stabilize soil. Other processes also occur simultaneously during treatment such as electrolysis, dissociation, sorption, and exchange mechanisms, etc. The aim of the research is to evaluate the effectiveness of the injection of stabilizing ions (Ca2+, CO32-, and HPO42-) in enhancing the shear strength of fine-grained soils. The shear strength of the soil increased up to 127% after treatment when measured near the anode and up to 495% when measured near the cathode. The results show that the proposed method can significantly increase soil strength; hence, it overcomes bearing capacity problems in soft fine-grained soils with low hydraulic conductivity.